MOVE FAST OR BUILD TIES? WHICH STRATEGY TRULY DRIVES MSME PERFORMANCE? (Lex localis - Journal of Local Self-Government, 2025)
How do small firms grow when markets shift? We surveyed 312 Micro, Small, and Medium Enterprises (MSMEs) in West Java and compared four simple “strategies” for turning capabilities into revenue growth: Agility-led, Relationship-led, Big-bet, and Dual-lever (relationships + scope + speed). For each firm, we estimated the four options and assigned the one that best explained its results. One pattern stood out: relationships with customers, suppliers, and local institutions matter most both directly and, even more, by helping firms diversify products, channels, and resources. Moving faster on its own was not a safe bet; speed helped only when combined with strong relationships and a clear plan to expand scope (the Dual-lever archetype). Sector patterns were modest: culinary firms tended to be Relationship-led, while technology firms were fully Dual-lever. We translate these findings into practical playbooks: build partner ties first, expand scope next, and add speed once the complements are in place.